The development of functional overreaching is associated with a faster heart rate recovery in endurance athletes - Aubry, A.; Hausswirth, C.; Louis, J.; Coutts, A. J.; Buchheit, M.; Le Meur, Y. (PLOS ONE, 2015)
Purpose: The aim of the study was to investigate whether heart rate recovery (HRR) may represent an effective marker of functional overreaching (f-OR) in endurance athletes.